PERENCANAAN MANAJEMEN KONSTRUKSI PADA GEDUNG MANGATA 4 LANTAI DI JALAN H. RAIS A. RACHMAN KELURAHAN SUNGAI JAWI KECAMATAN PONTIANAK KOTA, KOTA PONTIANAK. - F, Andra Rivandra; Silalahi, Feri; Nernawani, Nernawani; Reski, Indah Anjar (RETENSI, 2020)
The author carried out a construction management plan for the Mangata building which had previously been carried out by structural planning and drawing plans by (Muhammad Oki Try Hatmojo and Maulidya Anau Wiyah), Final Project for students of Pontianak State Polytechnic Diploma IV Civil Engineering Department 2019. Therefore, to realize the construction of the Mangata Building, proper construction management planning is required, so that results are in accordance with the requirements. Therefore, the authors plan an excellent project construction management system in an effort to accelerate the construction of the Mangata building which is the title of this final project. The method used in the discussion of construction management is in the form of a management system for cost, quality, time, human resources and occupational health safety in structural work which includes foundations, beams, columns and floor plates. Based on the results of the analysis of the method above, it is found that the cost of the structural work required to complete the work on the Mangata Building construction project is Rp. 28,007,395,396.25. The time it took to complete the work was 30 weeks for quality planning in the form of quality control and a list of specifications tables. Furthermore, for human resource planning in the form of organizational structure and workforce requirements as a means for good work implementation, while the planned K3 management planning is in the form of identification and control of K3 potential hazards to each type of work and costs for PPE and APK needs.